An update on current and emerging treatments for pulmonary arterial hypertension in childhood and adolescence. (1st February 2019) - Wacker, Julie; Weintraub, Robert; Beghetti, Maurice
ABSTRACT: Introduction : Pulmonary hypertension is a severe condition that can develop during childhood due to several different etiologies. During the last two decades, based on a better understanding of the underlying pathobiology leading to pulmonary arterial hypertension, targeted therapies have been developed and have improved the dreadful prognosis of the condition. However, curative therapy remains elusive. Areas covered : In this article, we will review the currently available drugs in pediatric pulmonary arterial hypertension and discuss the recommended management strategies. Expert commentary : Most of the drugtrials in pulmonary hypertension have been performed in adults, with extrapolation of the results to children. Most of the pediatric studies are non-controlled. The rarity of the disease and the lack of identifiable pediatric treatment goals and satisfactory trial end-points could explain the paucity of specific pediatric studies. An evolution has been made in the last few years regarding the treatment strategy of pulmonary arterial hypertension, with evidence that early combination therapy with at least two pulmonary vasodilators was beneficial on the survival. Children with pulmonary hypertension should be referred to experienced centers early, to benefit from a comprehensive initial assessment. Serial clinical and hemodynamic re-evaluation should assess treatment response and guide potential change in therapy.